THEORETICAL FOUNDATIONS OF MONETARY POLICY - Jurayev Iskandar Samadarovich; Sharipova Nigina Djurakulovna (International Journal of Innovations in Engineering Research and Technology, 2023)
It is natural for any country to worry about monetary policy for its political and economic future. This article describes the theoretical foundations of monetary policy in detail.